2017
DOI: 10.15446/dyna.v84n203.61549
|View full text |Cite
|
Sign up to set email alerts
|

Compostaje de biorresiduos: Tendencias de investigación y pertinencia en países en desarrollo

Abstract: Biowaste is the main fraction of MSW in developing countries. Composting is a promising alternative for the management of biowaste in these contexts. However, its implementation has not been effective in developing countries, for which it is necessary to explore options to improve its application in this context. This article reviewed the research trends on biowaste composting and the potential application in developing countries such as Colombia. For this purpose, the technology monitoring methodology was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
2
0
4
Order By: Relevance
“…Con relación al monitoreo de las pilas de compostaje, se midió diariamente la temperatura en el centroide y el perímetro de cada pila con un termómetro de carátula de 30 cm (Termómetro Reotemp, San Diego, California, EE.UU); la temperatura ambiente se registró con una termocupla TC spring loaded. Por otra parte, se midieron el pH, SV, NT y PT (Acosta-Durán et al, 2013;Oviedo-Ocaña et al, 2017) dos veces por semana hasta el inicio de la fase de enfriamiento, donde se redujo la frecuencia a una vez por semana.…”
Section: Monitoreo Del Proceso Y De La Calidad Del Productounclassified
See 2 more Smart Citations
“…Con relación al monitoreo de las pilas de compostaje, se midió diariamente la temperatura en el centroide y el perímetro de cada pila con un termómetro de carátula de 30 cm (Termómetro Reotemp, San Diego, California, EE.UU); la temperatura ambiente se registró con una termocupla TC spring loaded. Por otra parte, se midieron el pH, SV, NT y PT (Acosta-Durán et al, 2013;Oviedo-Ocaña et al, 2017) dos veces por semana hasta el inicio de la fase de enfriamiento, donde se redujo la frecuencia a una vez por semana.…”
Section: Monitoreo Del Proceso Y De La Calidad Del Productounclassified
“…Entre los MS se encuentran materiales como aserrín, residuos verdes, cascarilla de arroz, paja, entre otros (Li et al, 2013;Soto-Paz et al, 2017). El uso de residuos verdes es ampliamente documentado en la literatura (Li et al, 2013).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The use of amendment materials (AM) and bulking agents (BA) improves the characteristics of substrates with physicochemical limitations such as nutrient unbalance and high-water content, enhancing process conditions and end-product quality [3,19]. Woodchips, green waste, and rice straw are common BA; Woodchips (WC) are the most popular due to its TOC contribution and low water content [20,21]. On the other hand, recently, Oviedo-Ocaña et al [22] have shown the benefits of using biowaste (BW) as AM to provide the macro-and micronutrients needed to stimulate biological activity during the composting process.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the extensive research that has been carried out around the composting process for the control of environmental contamination and for obtaining a quality product, Onwosi et al [10]; Cerda et al [11] and Soto-Paz et al [12] explain that it is still necessary to carry out investigative efforts to analyze operational factors and deepen a better understanding of the biochemical phenomena of the process. Several researchers have reported that operational factors such as the mixture ratio (MR) between a substrate and a co-substrate and the turning frequency (TF) influence the composting process and product quality.…”
Section: Introductionmentioning
confidence: 99%